Performance of rabbits fed diets with varying concentrate and fodder ratio in north eastern region of Tripura - DAS, TAPAN KUMAR; PAL, SAUMEN KANTI; DE, ANKAN; KHUJUR, ANJILA T; DEBNATH, JOWEL; DEBNATH, BIKAS CHANDRA; CHAKRABARTI, ASIT (The Indian Journal of Animal Sciences, 2019)
A study on growth performance of 24 male New Zealand White (NZW) rabbits was conducted to work out an economical feeding system. Rabbits were randomly distributed into 4 groups of 6 animals each. Animals in group T1 were provided only concentrate mixture whereas in group T2, T3 and T4 were provided concentrate mixture and cowpea in ratio of 75:25, 50:50 and 25:75 on DM basis, respectively. The study was conducted for 42 days. From 28 day onwards, BW was higher in T1 followed by T2, T3 and T4. Total weight gain and ADG (g/d) were significantly higher in T1. Total DMI and DMI (g/d) were significantly higher in T4 than other groups. Feed efficiency was highest in T1 and lowest in T4. The average value of DM, CP, EE, TA and NFE digestibility were unaffected. But CF digestibility was significantly higher in T3 than T2. Blood urea and blood urea nitrogen (BUN) was significantly lower in T4 than other groups. Lowest cost of production and highest net profit/kg live weight of rabbit was observed in T1 than other groups. Net profit per rabbit was highest in T1 and lowest in T4. It was concluded that weight gain of about 12g/d can be achieved in NZW rabbit maintained either on concentrate mixture or concentrate mixture with cowpea in the ratio of 75:25 or 50:50 without any adverse effect in hot humid climate of Tripura.